Prototyping teams of affective agents in robocode - Rebelo, António (2015)
The study of the impact of emotion and affect in decision making processes involved in a working team stands for a multi-disciplinary issue (e.g. with insights from disciplines such as Psychology, Neuroscience, Philosophy and Computer Science). On the one hand, and in order to create such an environment we look at a team of affective agents to play into a battlefield, which present different emotional profiles (e.g. personality and mood). An emotional system, based on the OCC (Ortony, Clore and Collins) model, was proposed and implemented. As a way to integrate the personality of a robot with its emotions we used pleasure-arousal-dominance (PAD) model of mood. On the other hand, to attain cooperation, a voting mechanism and a decision-making process was implemented, being Robocode used as the simulation environment. Indeed, the results so far obtained are quite satisfying; the agent team performs quite well in the battlefield and undertakes different behaviours depending on the skirmish conditions